Perbandingan Sistem Hukum Indonesia dan Malaysia (International Forum of Researchers and Lecturers, 2025)
Indonesia and Malaysia, as two Southeast Asian nations with shared historical and cultural ties, possess distinct legal sistem shaped by their colonial legacies. Indonesia adheres to a civil law sistem (derived from Dutch jurisprudence), while Malaysia follows a common law framework (inherited from British rule). Nevertheless, both jurisdictions incorporate Islamic law and customary legal traditions into their national legal sistem. This study conducts a comparative analysis of the legal sistem of both countries, with a particular focus on criminal law, civil law, and judicial structures, while also examining the challenges and opportunities for legal harmonization in the context of ASEAN integration. The research employs a normative juridical methodology, utilizing statutory and doctrinal legal analysis. Findings indicate that the primary distinctions lie in their legal sources (codification versus precedent) and the role of judicial institutions, while similarities emerge in their recognition of legal pluralism. Harmonization efforts face structural, substantive, and cultural challenges, yet potential exists in areas such as digital law, environmental law, and Islamic inheritance law.